Kegagalan Pembangunan Ekonomi Indonesia Akibat Terperangkap Kegagalan Pendekatan Teori Ekonomi Pembangunan - Dumadi Tri Restiyanto; Nanang Yusroni (AKSES: Jurnal Ekonomi dan Bisnis, 2006)
Monetary crisis in Indonesia is due to the failure of the new order development planning under the Soeharto regime. Various capitalist economic development theories are making the stages of economic improvements to fall apart. The failure of Rostow’s theory and other development theories results in the failure of the development transportation process. Foreign debts are even higher due to economic dependence on developed nations. The development of that ought to bring a Trickle Down Effect is bringing a Back Wash Effect instead. Hence it is the growing poverty and rupiah’s weakening that is taking place instead of the anticipated economic lift off.